EKSTIRPASI LIPOMA LIDAH DENGAN PENDEKATAN MANDIBULOTOMI - Pelealu, Olivia C. P. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Lipoma is rarely found in the oral cavity. Actually, lipoma is a benign tumor but it will create an operational procedure problem if its size is big and it grows in a difficult location. This tumor is usually found at the age of 40 â€“ 60 years, more frequently in men, but the same for all races. Clinically, lipoma occurs as a mass with a smooth surface, yellowish to orange in color, and painless. The diagnosis of a lipoma is confirmed by using a CT scan that shows an irregular globular radioluscent mass with a clear border that seperates it from the surrounding tissues. The definite diagnosis should be based on a fine needle aspiration biopsy (FNAB) and a pathological examination. The management of an oral cavity lipoma is through an operation. We reported a case of a lipoma on the right side of the tongue of a 56-year-old male. The tumor was extirpated with a mandibulotomy approach, in which the mandible is cut to widen the operation field without removing the mandible bone. Keywords: lipoma, tongue, mandibulotomy, extirpation. Â Â Abstrak: Lipoma merupakan tumor yang jarang terjadi dalam kavum oris. Lipoma merupakan tumor jinak namun akan menimbulkan masalah bila berukuran besar dan tumbuh di lokasi yang sulit untuk dilakukan operasi. Tumor ini sering ditemukan pada usia 40-60 tahun, lebih sering pada laki-laki, dan sama untuk semua ras. Secara klinis lipoma tampak sebagai massa dengan permukaan licin, berwarna kekuningan sampai jingga, dan tidak nyeri. Diagnosis untuk lipoma dilakukan dengan CT scan yang memperlihatkan massa ireguler globuler, radiolusen, dan ireguler, serta berbatas jelas dari jaringan sekitarnya. Diagnosis pasti ditegakkan dengan fine needle aspiration biopsy (FNAB) dan pemeriksaan patologi. Penanganan lipoma dalam kavum oris yaitu dengan operasi. Kami melaporkan kasus seorang laki-laki berusia 56 tahun dengan lipoma lidah. Tumor tersebut diekstirpasi dengan pendekatan mandibulotomi, dimana mandibula dipotong untuk meluaskan lapangan pandang operasi tanpa mengangkat tulang mandibula. Kata kunci: lipoma, lidah, mandibulotomi, ekstirpasi.